MR imaging in neurocysticercosis: a study of 56 cases. - Martinez, H R; Rangel-Guerra, R; Elizondo, G; Gonzalez, J; Todd, L E; Ancer, J; Prakash, S S (American Journal of Neuroradiology, 1989)
We reviewed the MR findings in 56 patients with neurocysticercosis (NCC). MR findings were correlated with other neuroradiologic findings in 40 cases, with histopathologic studies in 15 surgically treated patients, and with autopsy findings in one case. Active NCC was characterized by the presence of a cyst in the brain parenchyma (53%) or in an intraventricular subependymal (22%) or subarachnoid (10%) location. The cysticercus appeared as a vesicle with a high-intensity signal nodule that corresponded to the scolex. Cyst mobility was observed in two intraventricular cases. Periventricular edema and ependymitis appeared as high-intensity signal on T2 sequences. Inactive NCC (15%) was characterized by calcifications (signal void on T1 and T2 sequences), aqueductal stenosis, and tissue thickness in the basal meninges. Degenerative cysticercus appeared on MR as an irregular vesicle without a scolex. Active NCC was better detected with MR than with CT (85% vs 21%), whereas inactive forms were observed better with CT (23% vs 14%). We conclude that MR is sensitive in the diagnosis of active NCC and may be useful in evaluating the degenerative changes in the parasite that occur as a result of natural degeneration, host response, or medical therapy.